On the American spider species formerly placed in Trachelas, with the proposal of the new genus Neochelas and a revision for southern South America (Araneae: Trachelidae) - Pett, Brogan L.; Grismado, Cristian J.; Baptista, Renner L.c.; Márquez, María E. González; Ramírez, Martín J. (Zootaxa, 2026)
The members of the trachelid spider genus Trachelas L. Koch, 1872 are taxonomically revisited in the Americas, and the fauna from southern South America is revised. The new genus Neochelas is diagnosed and described to accommodate these species, as well as six new species and 61 transferred species, making Neochelas the most diverse genus of trachelids with 67 nominal taxa. Four species are redescribed: N. robustus (Keyserling, 1891) comb. nov., N. rugosus (Keyserling, 1891) comb. nov., N. submissus (Gertsch, 1942) comb. nov., and N. vitiosus (Keyserling, 1891) comb. nov.; the males of N. submissus are described for the first time. Six new species are described from Argentina, Brazil, and Paraguay: N. amambay sp. nov., N. cerroleon sp. nov., N. calilegua sp. nov., N. gualamba sp. nov., N. iguazu sp. nov., and N. itapua sp. nov. Neochelas niger (Mello-Leitão, 1922) comb. nov. and Neochelas tridentatus (Mello-Leitão, 1947) comb. nov. are transferred from Trachelas and considered nomina dubia due to insufficient descriptions and descriptions based on immature specimens; their types are illustrated here. The remaining new combinations proposed (from Trachelas to Neochelas) are the following: Neochelas amacayacu (Sherwood & Arzuza Buelvas, 2025), Neochelas anomalus (Taczanowski, 1874), Neochelas barroanus (Chamberlin, 1925), Neochelas bicolor (Keyserling, 1887), Neochelas bispinosus (F. O. Pickard-Cambridge, 1899), Neochelas borinquensis (Gertsch, 1942), Neochelas bravidus (Chickering, 1973), Neochelas bulbosus (F. O. Pickard-Cambridge, 1899), Neochelas cadulus (Chickering, 1973), Neochelas cambridgei (Kraus, 1955), Neochelas contractus (Platnick & Shadab, 1974), Neochelas crassus (Rivera-Quiroz & Alvarez-Padilla, 2015), Neochelas daubei (Schmidt, 1971), Neochelas depressus (Platnick & Shadab, 1974), Neochelas digitus (Platnick & Shadab, 1974), Neochelas dilatus (Platnick & Shadab, 1974), Neochelas ductonada (Rivera-Quiroz & Alvarez-Padilla, 2015), Neochelas ecudobus (Chickering, 1973), Neochelas erectus (Platnick & Shadab, 1974), Neochelas femoralis (Simon, 1898), Neochelas fuscus (Platnick & Shadab, 1974), Neochelas giganteus (Platnick & Shadab, 1974), Neochelas gloriamarielae (Chamé-Vázquez & Chamé-Vázquez, 2025), Neochelas hamatus (Platnick & Shadab, 1974), Neochelas hassleri (Gertsch, 1942), Neochelas huachucanus (Gertsch, 1942), Neochelas inclinatus (Platnick & Shadab, 1974), Neochelas jamaicensis (Gertsch, 1942), Neochelas lanceolatus (F. O. Pickard-Cambridge, 1899), Neochelas latus (Platnick & Shadab, 1974), Neochelas mexicanus (Banks, 1898), Neochelas mombachensis (Leister & Miller, 2015), Neochelas mulcetus (Chickering, 1973), Neochelas oculus (Platnick & Shadab, 1974), Neochelas odoreus (Rivera-Quiroz & Alvarez-Padilla, 2015), Neochelas organatus (Platnick & Shadab, 1974), Neochelas pacificus (Chamberlin & Ivie, 1935), Neochelas panamanus (Chickering, 1937), Neochelas parallelus (Platnick & Shadab, 1974), Neochelas planus (Platnick & Shadab, 1974), Neochelas prominens (Platnick & Shadab, 1974), Neochelas quadridens (Kraus, 1955), Neochelas rotundus (Platnick & Shadab, 1974), Neochelas santaemartae (Schmidt, 1971), Neochelas similis (F. O. Pickard-Cambridge, 1899), Neochelas sinuosus (Platnick & Shadab, 1974), Neochelas speciosus (Banks, 1898), Neochelas spicus (Platnick & Shadab, 1974), Neochelas spinulatus (F. O. Pickard-Cambridge, 1899), Neochelas spirifer (F. O. Pickard-Cambridge, 1899), Neochelas tomaculus (Platnick & Shadab, 1974), Neochelas tranquillus (Hentz, 1847), Neochelas transversus (F. O. Pickard-Cambridge, 1899), Neochelas triangulus (Platnick & Shadab, 1974), Neochelas trifidus (Platnick & Shadab, 1974), Neochelas truncatulus (F. O. Pickard-Cambridge, 1899), and Neochelas volutus (Gertsch, 1935). Finally, we propose the new combination Trachelopachys nigrifemur (Mello-Leitão, 1941) comb. nov., transferred from Trachelas. After this study, we propose that Trachelas does not occur in the Americas. We present a phylogenetic analysis of Trachelidae based on six genetic markers, confirming the monophyly of Neochelas and showing that it is not closely related to Trachelas sensu stricto.